Hybrid sorubim viscera protein concentrate in the diets for barred sorubim - Hisano, Hamilton; Fonseca, Gustavo Graciano; Russo, Marcia Regina; Lopes Della Flora, Marco Aurelio; Ishikawa, Marcia Mayumi; Padua, Santiago Benites de [UNESP] (Inst Pesca, 2013)
The current study evaluated the growth performance and the haematological profile of barred sorubim fed with levels of hybrid sorubim viscera protein concentrate (0.0; 5.0; 10.0 e 15.0%) in isoprotein and isoenergetic diets. Eighty fish with an average initial weight of 39.8 +/- 0.28 g and an average initial length of 19.92 +/- 0.25 cm were distributed in 16 aquaria of 60 L, with recirculation system and temperature control, during 35 days. The experimental design was completely randomized with four treatments and four replications. For the growth performance assay were analyzed the follows variables: weight gain (WG), feed consumption (FC), apparent feed conversion ratio (AFCR) and protein efficiency ratio (PER). Furthermore, the hemogram were assessed on the treated fish with levels of protein concentrate. It was observed no significant difference (P > 0.05) for all the parameters evaluated. It was concluded that the protein concentrate from hybrid sorubim viscera can be included up to 15% in diets for barred sorubim juveniles without negative response on the performance and health.
Keywords: Carnivorous fish; coproduct; hemogram; protein; Pseudoplatystoma corruscans; P.reticulatum